KAJIAN TENTANG RANCANG BANGUN BENTENG KOMPENI DI JEPARA - Novida Abbas (BRIN, 1994)
One of the means of defense dating from the colonial period in Java is the Dutch fortresses, some of which can still be seen today. The existence of these fortresses implied a conflict between community groups in the archipelago against the colonialists, which forced the colonial side to establish various means of defense to counter the people's struggle. Among a number of former Dutch forts in Java, one that can still be seen is a fort located in Jepara. This fort, known as Benteng VOC or Benteng Kompeni, is located in Ujung Batu Village, Jepara District, Jepara Regency, Central Java Province. To be precise, the fort was located at the top of a hill overlooking the Java Sea.